Pregnancy Associated Plasma Protein-A (PAPP-A) as a Marker to Distinguish Normotensive with Early 2nd Trimester and Late 3rd Trimester Onset of Preeclampsia - Ragam Pesona Simangunsong; Herman Kristanto; Mirza Iskandar; Syarief Thaufik; Besari Adi Pramono; Arufiadi Anityo Mochtar (RSUP Dr. Kariadi, 2024)
Introduction: Preeclampsia is a hypertensive condition that occurs after 20 weeks of gestation accompanied by target organ damage. Complications of preeclampsia can cause intrauterine fetal growth retardation, and placental hypoperfusion, even in the most serious situations, namely termination of pregnancy and death of the fetus and/or mother. Pregnancy-associated plasma protein-A (PAPP-A) is a high molecular weight glycoprotein that is produced in the placenta and secreted into the maternal bloodstream. However, based on several studies that have been conducted, there is uncertainty in the results of assessing PAPP-A levels obtained in pregnant women in the second and third trimesters. Aim: Proving differences in PAPP-A levels in the second and third trimesters in the incidence of early-onset preeclampsia and normotensive pregnancy. Methods: An analytic observational study with a cross-sectional approach was carried out in the delivery room of RSUP Dr. Kariadi Semarang, Halmahera Health Center, Ngesrep Health Center, Bulu Health Center, and private midwife practice in Semarang City. The subjects of the study were six 2nd-trimester preeclampsia patients, fourteen 3rd-trimester preeclampsia patients, and twenty normotensive pregnancy patients who met the inclusion and exclusion criteria. Data were analyzed using Mann Whitney with a significance of p<0.05 Results: There was a significant difference in PAPP-A levels (p<0.001) between the preeclampsia and normotensive pregnancy groups, whereas PAPP-A levels were higher in the preeclampsia group. There were significant differences in PAPP-A levels (p<0.001) between the 2nd-trimester preeclampsia, 3rd-trimester preeclampsia, and normotensive pregnancies, where the highest PAPP-A levels were found in the 2nd-trimester preeclampsia group. Conclusion: There was a significant difference in PAPP-A levels between the second and third trimesters of early-onset preeclampsia compared to normotensive pregnancies, where PAPP-A levels were higher in the second and third trimesters of early-onset preeclampsia. Elevated PAPP-A levels in the second and third trimesters are associated with an increased risk of early-onset preeclampsia.